1997
DOI: 10.1021/la962047x
|View full text |Cite
|
Sign up to set email alerts
|

Coadsorption of Poly(styrenesulfonate) and Cetyltrimethylammonium Bromide on Silica Investigated by Attenuated Total Reflection Techniques

Abstract: Adsorption of poly(styrenesulfonate) (PSS) and cetyltrimethylammonium bromide (CTAB) on silica from mixed solutions of the polyelectrolyte and surfactant has been studied. The surface excess of the polyelectrolyte was determined by ultraviolet attenuated total reflectance (UV-ATR) monitoring of the 224 nm styrenesulfonate absorbance band. Complementary information was derived from infrared attenuated total reflectance (IR-ATR) on the same system. Deconvolution of the 2920 cm-1 asymmetric and 2850 cm-1 symmetri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 21 publications
(22 reference statements)
4
59
2
Order By: Relevance
“…Although the intensity of a maxima at 224 nm is greater than that at 261 nm (about 18 times), these peaks are specific wavelengths for benzene sulfonate group. They are in good agreement with the values of maximum absorbance in published papers [17,19]. Figure 2 also shows that the magnitude of all UV spectra of PSS does not change significantly at a given concentration of PSS.…”
Section: Spectra Of Pss In the Absence And Presence Of Sdssupporting
confidence: 87%
See 1 more Smart Citation
“…Although the intensity of a maxima at 224 nm is greater than that at 261 nm (about 18 times), these peaks are specific wavelengths for benzene sulfonate group. They are in good agreement with the values of maximum absorbance in published papers [17,19]. Figure 2 also shows that the magnitude of all UV spectra of PSS does not change significantly at a given concentration of PSS.…”
Section: Spectra Of Pss In the Absence And Presence Of Sdssupporting
confidence: 87%
“…As mentioned above, polyanion PSS was chosen in various studies for coadsorption with surfactant because it has a high charge density statistically distributed along the backbone of polymer and the benzenesulfonate groups that are strong ultraviolet (UV) chromophores [19]. The individual adsorption of PSS and surfactants or mixture adsorption on metal oxide has been addressed through different measurements of adsorption density, zeta potential, fluorescence spectrophotometry, electrospin resonance (ESR), and attenuated total reflection techniques with ultraviolet or infrared spectroscopy [16][17][18][19]. Furthermore, Wolterink et al [20] indicated that the charge regulation of metal oxide upon adsorption of strong electrolyte was obtained theoretically and experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…Absorptions in the UV‐vis spectra of the PAH/MWNT multilayer films assembled on quartz slides (double sides) generally shift to higher values over the whole measured range (200–600 nm) as a function of assembly number (See Figure S1 in the Supporting Information ). In addition an emergence and intensification of the peaks at 224 and 267 nm, which are assigned to the absorbance of the phenyl groups of PSS and MWNTs, respectively, is observed (see Figure S2 in the Supporting Information for UV‐vis spectra of MWNTs suspended in water) 6b,13. The universal increase of the absorbance is a hint for the successful assembly of the MWNTs since they absorb lights of all the wavelengths in the measured region.…”
Section: Resultsmentioning
confidence: 84%
“…The large surface area of the platelet faces, and their negative charge, may favor the aggregation of cationic surfactant molecules as hemimicelles and micelles. Recently, the interaction of cetyltrimethylammonium bromide (CTAB) with model surfaces such as silica, titanium dioxide, and mica has been probed using several techniques, including atomic force microscopy, 12,13 attenuated total reflectance Fourier transform infrared (spectroscopy), 14,15 and optical reflectometry. 13 Furthermore, some studies have looked at the coadsorption of both anionic and cationic surfactants.…”
Section: Abend and Lagalymentioning
confidence: 99%